Bianchi type-V cosmological models with perfect fluid and heat flow in Saez-Ballester theory - Ram S.; Zeyauddin M.; Singh C.P. (My University, 2025)
In this paper we discuss the variation law for Hubble's parameter with average scale factor in a spatially homogeneous and anisotropic Bianchi type-V space-time model, which yields constant value of the deceleration parameter. We derive two laws of variation of the average scale factor with cosmic time, one is of power-law type and the other is of exponential form. Exact solutions of Einstein field equations with perfect fluid and heat conduction are obtained for Bianchi type-V space-time in these two types of cosmologies. In the cosmology with the power-law, the solutions correspond to a cosmological model which starts expanding from the singular state with positive deceleration parameter. In the case of exponential cosmology, we present an accelerating non-singular model of the Universe. We find that the constant value of deceleration parameter is reasonable for the present day Universe and gives an appropriate description of evolution of Universe. We have also discussed different types of physical and kinematical behaviour of the models in these two types of cosmologies. © Indian Academy of Sciences.